2003
DOI: 10.1161/01.hyp.0000098661.37637.89
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Endothelial Dysfunction by Selective Estrogen Receptor-α Stimulation in Ovariectomized SHR

Abstract: Abstract-Both known estrogen receptors, ER␣ and ER␤, are expressed in blood vessels. To gain further insight into the role of ER␣ in a functional setting, we investigated the effect of the novel highly selective ER␣ agonist Cpd1471 on vascular reactivity in ovariectomized spontaneously hypertensive rats (SHR). After ovariectomy or sham operation, 12-week-old female SHR received either 17␤-estradiol (E2, 2 g/kg body wt per day), the selective ER␣ agonist Cpd1471 (30 g/kg body wt per day), or placebo. Acetylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 59 publications
(41 reference statements)
4
54
1
1
Order By: Relevance
“…In line with previous observations, E2 efficiently attenuated cardiac hypertrophy in ovariectomized young SHRs, but blood pressure levels were not significantly different among all of the groups of young SHRs. 10,19 These findings indicate that estrogens are able to attenuate cardiac growth also by direct and blood pressure-independent mechanisms, such as cardiac ANP expression and mitogen-activated protein kinase activation, as we and others have reported before. 20 But in contrast to young animals, estrogen substitution failed to attenuate cardiac hypertrophy in aged SHRs.…”
Section: Discussionsupporting
confidence: 76%
“…In line with previous observations, E2 efficiently attenuated cardiac hypertrophy in ovariectomized young SHRs, but blood pressure levels were not significantly different among all of the groups of young SHRs. 10,19 These findings indicate that estrogens are able to attenuate cardiac growth also by direct and blood pressure-independent mechanisms, such as cardiac ANP expression and mitogen-activated protein kinase activation, as we and others have reported before. 20 But in contrast to young animals, estrogen substitution failed to attenuate cardiac hypertrophy in aged SHRs.…”
Section: Discussionsupporting
confidence: 76%
“…21 In premenopausal women, a differential ratio of ET A to ET B receptors has also been found, favoring a vasodilator effect of endothelin via ET B receptors. 22 In recent animal studies, estradiol 23 or its metabolites 24 have been shown to inhibit endothelin synthesis and improve endothelial dysfunction in ovariectomized female spontaneously hypertensive rats 25 and DOCA-salt hypertensive rats. 23 Therefore, estrogens should be cardiovascular protective because of their positive effect on endothelin inhibition.…”
Section: Estrogen: "Good Girl"mentioning
confidence: 99%
“…The findings that cardiovascular risk increases when estrogen production ceases and that ovariectomy prevents the more beneficial outcome of volume overload or aging in females argues in favor of a protective role of estrogen. 3,4 In contrast, the finding that estradiol-treated female rodents have a greater post-MI rate of death argues against a protective role. 5,6 Recent human studies on hormone replacement therapy similarly question the cardioprotective role of estrogen.…”
mentioning
confidence: 99%